Standardization of inoculation method in nursery beds and management of sheath blight of rice through host resistance, chemicals and botanicals - and D.S. DODAN, RAM SINGH*, S. SUNDER (Indian Phytopathology, 2010)
Amongst six inoculum sources of Rhizoctonia solani and different ages of rice seedlings (10-60 days) evaluatedto induce sheath blight in nursery, maximum disease incidence and severity was recorded in 30-40 days old seedlings innursery with the inoculum raised on barley grains + Typha pieces closely followed by barley grains and rice grains inocula. Out of 182 rice genotypes screened, five genotypes viz. HKR 99-103, HKR 2000-26, HKRH-1059, HRI 126 and IR 64683-87-2-2-3-3 were found to be moderately resistant to sheath blight in nursery while in field, two genotypes HKR 2000-514 and IR 64683-87-2-2-3-3 proved resistant and three genotypes HKR 99-103, HKR 2001-537 and HKRH-1059 were moderately resistant. Only three genotypes namely, HKR 99-103, HKRH-1059 and IR 64683-87-2-2-3-3 showed resistant/moderate resistant reaction both under nursery and field conditions. Though, there was a positive correlation between nursery and field screening tests, but nursery screening was not found an absolute indication of resistance in the field. However, it can be utilized in short listing of rice genotypes for screening against sheath blight in the field. Out of seven fungitoxicants and two antibiotics, diniconazole (Sumi-8 25 WP) and hexaconazole (Contaf 5 EC) were found to be the most effective treatments in reducing sheath blight and enhancing grain yield of paddy. Amongst botanical formulations and plant extracts, Spictaf and Tricure slightly reduced the disease severity 10 days after spraying. However, these treatments had no significant effect on disease severity recorded 25 days after spraying and on grain yield of paddy. Out of seven non-conventional chemicals, maleic acid and zinc sulphate significantly reduced the disease severity without any significant increase in grain yield of paddy.